Experiences With an Intervention Based on Geriatric Assessment With Management: A Qualitative Study - May Ingvild Volungholen Sollid; Line Melby; Marit Slaaen; Grethe Eilertsen; Inga Marie Røyset; Øyvind Kirkevold (Nursing Open)
ABSTRACT Aims To describe: (i) Experiences of older patients with cancer after receiving an intervention based on geriatric assessment with management. (ii) Experiences of cancer nurses in municipal health care from implementing an intervention based on geriatric assessment with management and their perspectives on the intervention. Design A qualitative, descriptive interview study reported according to COREQ. Methods The sample comprises five men and three women with cancer, mean age 75 years, and 11 female cancer nurses. Data collection was performed as individual patient interviews, and individual and small group interviews with cancer nurses. Inductive, thematic analysis was performed. Results Three main themes were generated: Systematic approach, Patient‐centeredness and Regular and professional contact. Patient or Public Contribution Participants did not review transcripts, participate in analysis, or review results. This was not deemed appropriate, as all interviews were analysed as a whole. User representatives participated in the planning and conducting of the intervention study and implementation procedures. Trial Registration ClinicalTrials.gov Identifier: NCT03881137